Fabrication of Germanium Detectors by Using Nd-YAG Laser - Al-Dahan, Ziad Tarik; Abduljabbar, Layth Mokhles (Nahrain University College of Engineering Journal, 2017)
Germanium detectors were fabricated by doping n-type germanium samples with boron. Boron powder was spread over germanium and bombard with Nd: YAG laser of wavelength 1064nm at different energies of (200,500)mJ to diffused the boron atoms inside the germanium wafer. Different measurements were carried out to characterize the detector made.